2013
DOI: 10.1161/circulationaha.113.004634
|View full text |Cite
|
Sign up to set email alerts
|

Novel Small Leucine-Rich Repeat Protein Podocan Is a Negative Regulator of Migration and Proliferation of Smooth Muscle Cells, Modulates Neointima Formation, and Is Expressed in Human Atheroma

Abstract: Background SMC migration and proliferation critically influence the clinical course of vascular disease. We tested the effect of the novel small leucine-rich repeat protein podocan on SMC migration and proliferation using a podocan deficient mouse in combination with a model of arterial injury and aortic explant SMC culture. In addition, we examined the effect of overexpression of the human form of podocan on human SMC and tested for podocan expression in human atherosclerosis. In all these conditions we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…ECM molecules are highly effective modulators of cell functions, such as migration and proliferation [32]. Given the inhibitory effect of high podocan levels on smooth muscle cell (SMC) proliferation [33], PODN may also be involved in cell proliferation regulation, which requires further experimental validation. Ras homolog family member J (RHOJ), a member of the Rho GTPase family, acts as a molecular switch by regulating cell functions, such as migration and proliferation, correlating well with increased cell motility and invasiveness [34].…”
Section: Discussionmentioning
confidence: 99%
“…ECM molecules are highly effective modulators of cell functions, such as migration and proliferation [32]. Given the inhibitory effect of high podocan levels on smooth muscle cell (SMC) proliferation [33], PODN may also be involved in cell proliferation regulation, which requires further experimental validation. Ras homolog family member J (RHOJ), a member of the Rho GTPase family, acts as a molecular switch by regulating cell functions, such as migration and proliferation, correlating well with increased cell motility and invasiveness [34].…”
Section: Discussionmentioning
confidence: 99%
“…In normal kidneys, podocan shows a distribution along the basement membrane of the glomeruli and proximal tubules [ 604 ], and more recent studies have shown that podocan is a constituent of human aortic tissue [ 607 ]. In agreement with its tissue distribution, podocan has been identified as a negative regulator of migration and proliferation of smooth muscle cells [ 608 ]. On this basis, podocan can affect atherosclerosis development like other SLRPs, such as biglycan.…”
Section: Small Leucine-rich Proteoglycans/slrpsmentioning
confidence: 93%
“…On this basis, podocan can affect atherosclerosis development like other SLRPs, such as biglycan. Of note, Podn −/− smooth muscle cells exhibit a constitutively-activated Wnt pathway, whereas wild-type smooth muscle cells overexpressing podocan have a significantly depressed Wnt signaling pathway [ 608 ], biological properties also shared by other SLRPs (see above). As in the case of other-non canonical SLRPs, podocan shares functional properties with decorin and biglycan, especially in its ability to bind collagen I and to induce p21 WAF1 and growth suppression [ 605 ].…”
Section: Small Leucine-rich Proteoglycans/slrpsmentioning
confidence: 99%
“…In fact, podocan is strongly and selectively expressed in the arteries of wild-type mice after injury. Podocan-deficient mice show increased arterial lesion formation in response to injury compared with their wild-type littermates [ 4 6 ]. In addition, the podocan-deficient mice are characterized by an increase in SMC proliferation, and this effect is exerted through the activation of the Wnt- β -catenin pathway in the SMCs both in vitro and in vivo [ 6 ].…”
mentioning
confidence: 99%